The Effect Of Project Based Learning Approach On Achivement And Perception About Learning Environment - İbrahim Erdoğan (Sakarya University, 2013)
Early childhood and Turkish Linguistic Education Program students that enrolled fall semester at faculty of education at Mus Alparslan University participated the study. Project based learning were used in these classrooms. Purpose of the study was to analyze project based learning approach effects on achivement and perception about learning environment. Both qualitative and quantitative methods were used in this study. To analyze pre-service teachers' perceptions about project based learning environment, Constructivist Learning Environment Survey collected as pre-test and post-test at the begining and at the end of semester. Interview was conducted with pre-service teachers at the end of the study. The result of the study revealed that project based learning lead learning, encourage research, enables student make causal connections between real life problems and learned contents, construct their own knowledge and simply facilitate effective and meaningful learning.